Power Domination of Media Owners in The Discussion of Updating The Broadcasting Law - Mokhammad Naigam Mahriva; Eka Wenats Wuryanata (Jurnal Penelitian Komunikasi dan Opini Publik, 2021)
The majority of digital players in Indonesia are under the control of social media, especially users of OTT services. This has led to the migration of conventional service users to OTT services on a number of digital platforms such as YouTube, Netflix, Facebook, Whatsapp, Instagram, Line and Muflix. The lawsuit is addressed to Article 1 paragraph 2 of Law No. 32 of 2002 concerning Broadcasting. The applicants came from INews TV and RCTI who considered the legal consistency of internet-based broadcasting to be very unstable. The issues reviewed are regarding the lawsuit by RCTI and Inews against the Broadcasting Law from a political economy perspective. This study aims to reveal the reality, especially the domination of power, behind the discourse on changing the law on broadcasting. This study was conducted qualitatively with methods, text analysis, primary, secondary data collection and in-depth interviews by political economists. The results showed that the lawsuit filed by RCTI and INews from the perspective of political economists has the result that the dominance of the power of media owners has an important role as a means of generating news / issues that are favorable to them.